Machinability baja AISI 1040 pada proses bubut dengan variasi cutting speed dan feed rate - AAIA Sri Komaladewi; DNK Putra Negara (Jurnal Energi Dan Manufaktur, 2006)
In order to obtain desired results of machining process (turning), parameter of process and material characteristic to be machined should be well known. This is due to different machining conditions and material yield different material machinability as well. It is needed to investigate of material machinability (AISI 1040) such as force, power and shear angle under different cutting speed (80, 160 and 240 m/min) and feed rate (0.1, 0.2, and 0.3 mm/rev). The results of investigation show that; at the same cutting speed the higher feed rate the higher cutting force needed; the higher cutting speed and feed rate, the higher power needed; at feed rate 0.1 mm./rev and 0.3 mm/rev, the higher cutting speed the shear angles has a trend to incline; at feed rate 0.2 mm/rev, cutting speed from 80 to 160 m/min yield increasing of shear angle, however, from 160 to 240 m/min shear angle declines.